Peran Guru Bimbingan dan Konseling (BK) dalam Mengembangkan Kepercayaan Diri dan Kesejahteraan (Well Being) Siswa - Nada Afifah; Fauziah Nasution (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Every person constantly wishes and works toward attaining psychological well-being for themselves. It is necessary for the individual to be able to receive in order for them to acquire psychological well-being.  This research was carried out with the intention of having an in-depth discussion on the topic of growing well-being in self-confidence with psychological well-being in the student population of SMP Negeri 6 Percut Sei Tuan. In this study, a qualitative research design with a descriptive method was used, with participants observing, being interviewed, and documenting their experiences. Three kids from grade seven at SMP Negeri 6 Percut Sei Tuan participated in this research as the study's subjects. In this work, the method of data analysis makes use of data analysis techniques created by Miles and Huberman. In this particular paradigm, analysis is comprised of the following steps: data reduction, data display, and conclusion and verification. According to the findings of this study, a healthy level of self-confidence is associated with 1) the condition of students self-confidence a low self-confidence attitude, does not dare to express opinions, does not dare to ask questions when not understanding the lesson, hesitating when speaking in front of the class, and is silent when appointed by the teacher to come to the front of the class. 2) the condition of students' self-confidence has a high self-confidence attitude, do not dare to ask questions when not understanding the lesson, and ask questions when not understanding the lesson. 2) The role that BK teachers play in boosting their students' self-confidence starts with the development of information service programs, the clarification of each student's situation, and the provision of information on how to boost their students' self-esteem.